Philosophy of Educational Policy: Problems, Challenges, and Possibilities - Rachmadani, Fadhila; Ahmad, Norainie (Universitas Negeri Yogyakarta, 2025)
Educational policy is a conceptual basis that is essential for the implementation of education. Educational policy also holds an important position, role, and function in the implementation of education at the micro, meso, and macro scales. This article focuses on the problems, challenges, and future possibilities regarding educational policy from a philosophical perspective. This paper aims to explore the problems, challenges, and various future possibilities in the field of educational policy through the lens of philosophy, specifically ontology, epistemology, and axiology. This literature-based paper is a qualitative study that refers to John Ward Creswell 's book entitled